Recent advances in metal catalyst- and oxidant-free electrochemical C-H bond functionalization of nitrogen-containing heterocycles - Li, Ya-Nan; Wang, Bin; Huang, Ye-Kai; Hu, Jin-Song; Sun, Jia-Nan (Frontiers in Chemistry, 2022)
The C-H functionalization of nitrogen-containing heterocycles has emerged as a powerful strategy for the construction of carbon-carbon (C-C) and carbon-heteroatom (C-X) bonds. In order to achieve efficient and selective C-H functionalization, electrochemical synthesis has attracted increasing attention. Because electrochemical anodic oxidation is ideal for replacing chemical reagents in C-H functionalization reactions. This mini-review summarizes the current knowledge and recent advances since 2017 in the synthetic utility of electrochemical transformations for the C-H functionalization of nitrogen-containing heterocycles.